Effects of Patients Satisfaction Towards Behavioural Intentions of Doctors and Health Care Services In Hospital - Muhammad Amin Khan, Naeem Amjad, Syed Ahmed Mahmud, Zain Gulzar, Fatima Aslam, Farrukh Sarrfraz (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Worldwide competition on a rising segment drives the interest of patients and makes them more on edge towards the conveyance of healthcare administrations. The developing concern approximately wellbeing and elevated financial levels of present day civilization have escalation moved forward the healthcare demands and moved patterns of the population towards accomplishing a more advantageous way of life. Patient fulfillment could be a measure of the degree to which a patient is content with the health care they received from their health care provider. Persistent fulfillment is one of the foremost important factors to decide the victory of a wellbeing care facility Objective: To study the effects of patient’s satisfaction towards behavioural intentions of doctors and health care services in hospital Study design: Quantitative cross sectional Settings: Niazi welfare foundation teaching Hospital Sargodha Duration: Four months i.e. 1st May 2022 to 30th August 2022 Data Collection procedure: A pre validated questionnaire was used. Study was carried out at outdoor patient department of Niazi welfare foundation teaching Hospital Sargodha. The total numbers of patients were 250 who participated after taking the informed consent. The study was done by simple random sampling technique. Detailed information was given to patient about the current research. Confidentiality of the participants was prioritized. Questionnaire consists of three constructs. Demographic profile, Patients Satisfaction level about behavioural Intentions of Doctors and Patients Satisfaction level about Outdoor patient department Results: The total number of patients who were participated in the study was 250 in which 140 (56%) were males and 110 (44%) were females. Variables including Patients Satisfaction level about behavioural Intentions of Doctors and Patients Satisfaction level about Outdoor patient department rated high. Results were shown in numbers and percentage in tables. Highest percentage include health care provider listen carefully, privacy insured, give management plan and doctor is professional as 88%, 94%, 96% and 84% while tests advice by 42% at lowest regarding Patients Satisfaction level about behavioural Intentions of Doctors. For convenience to reach pharmacy, laboratory facility and appropriate sign and arrows as 82%, 94% and 79% while proper wash room facility were marked as lowest 52% regarding outdoor patient environment at hospital. Conclusion: This study identifies the relationship between healthcare services and understanding fulfillment with the directing part of the physician’s behavior. The findings of the study appeared that patients were fulfilled with health care services. It is concluded that the way better and best healthcare services play a vital part in patient satisfaction. The finding of this study is very supportive in the event that they are transferred into activities for moving forward the quality of wellbeing care. Keywords: patient satisfaction, hospital, behavioural intention, health care, doctor